Water column methanotrophy controlled by a rapid oceanographic switch - Steinle, Lea; Graves, Carolyn A.; Treude, Tina; Ferré, Benedicte; Biastoch, Arne; Bussmann, Ingeborg; Berndt, Christian; Krastel, Sebastian; James, Rachel H.; Behrens, Erik; Böning, Claus W.; Greinert, Jens; et al. (Nature Geoscience, 2015)
Accepted manuscript version. Published version available at https://doi.org/10.1038/NGEO2420 . Large amounts of the greenhouse gas methane are released from the seabed to the water column, where it may be consumed by aerobic methanotrophic bacteria. The size and activity of methanotrophic communities, which determine the amount of methane consumed in the water column, are thought to be mainly controlled by nutrient and redox dynamics. Here, we report repeated measurements of methanotrophic activity and community size at methane seeps west of Svalbard, and relate them to physical water mass properties and modelled ocean currents. We show that cold bottom water, which contained a large number of aerobic methanotrophs, was displaced by warmer water with a considerably smaller methanotrophic community within days. Ocean current simulations using a global ocean/sea-ice model suggest that this water mass exchange is consistent with short-term variations in the meandering West Spitsbergen Current. We conclude that the shift from an offshore to a nearshore position of the current can rapidly and severely reduce methanotrophic activity in the water column. Strong fluctuating currents are common at many methane seep systems globally, and we suggest that they affect methane oxidation in the water column at other sites, too.